On Constructing an EPS Measure: An Assessment of the Properties of Dilution* - SCOTT, THOMAS W.; WIER, HEATHER A. (Contemporary Accounting Research, 2000)
Abstract This paper evaluates the information content of the treasury stock method for computing diluted earnings per share (EPS). We demonstrate that the treasury stock method decreases the annual association between earnings changes and stock returns and explain why this is the case. Further, we show that the treasury stock method leads to a dilutive adjustment that biases the random walk model of annual earnings in a predictable direction. Finally, we demonstrate that using the treasury stock method appears to confuse both analysts and investors: analysts' forecast errors increase with the size of the dilutive adjustment, and the association between unexpected earnings and stock returns at the earnings announcement date weakens as the dilutive adjustment increases.